Piloting a real-time surface water flood nowcasting system for enhancing operational resilience of emergency responders [Abstract] - Dapeng Yu; Mingfu Guan; Robert Wilby; Wright Bruce; Mark J. Szegner (2017)
Piloting a real-time surface water flood nowcasting system for enhancing operational resilience of emergency responders [Abstract]